Scattering and dissociative adsorption of H2 on the armchair and zigzag edges of graphite - Arboleda, Nelson B., Jr. (Animo Repository, 2004)
We performed quantum dynamics calculations on the scattering and dissociative adsorption of hydrogen molecules incident on the armchair and zigzag edges of graphite layers, using relevant potential-energy surfaces (PESs) recently obtained by Diño et al. [e-J. Surf. Sci. Nanotech. 2, 77 (2003), and references therein]. By employing the coupled channel method to determine the reflection and sticking probabilities, we compared the hydrogen scattering and dissociative adsorption dynamics on the two graphite surfaces. Our findings show the different scattering behaviors of H2 for the armchair edge and for the zigzag edge, which enable the identification of an unknown graphite edge from its interaction with H2. The scattering on the zigzag edge is due to the highly curved region of the PES reaction path for H2 interacting with the zigzag edge, whereas the scattering for the armchair edge is caused by a potential barrier. The reflection probability initially decreases with increasing the kinetic energy in both cases but gradually increases for the zigzag edge. Our findings also indicate that the zigzag edge can adsorb hydrogen better than the armchair edge, mainly due to the absence (presence) of an activation barrier in the zigzag (armchair) edge. There is a very weak dependence of the sticking probability on the initial vibrational state of H2 for both graphite edges. The difference in the vibrational effect is due to the relative position of the curved region with respect to the potential barrier (well). © 2004 American Institute of Physics.